The Empirical Evaluation of How Public Expenditure Influences Economic Growth in Nigeria (Global Journal of Management and Business Research, 2020)
This study examined government expenditure and economic growth in Nigeria during the period 1985-2015. The specific objective of this study is to investigate how government capital expenditure affects economic growth in Nigeria. Data extracts from the Central Bank of Nigeria (CBN) statistical bulletin form our major source of information. We use the Unit root test using Augmented Dickey-Fuller test technique. Our result revealed that all the variables in the model were stationary at different levels of test. The Johansson co-integration test result also showed that all the variables in the model have a long-run relationship, and government capital expenditure has a positive and significant impact on economic growth in Nigeria. The government recurrent expenditure also has a positive and significant impact on economic growth in Nigeria having a coefficient of determination of 98.4% variation in the dependent variable being explained by changes in the explanatory variables. Based on our findings, we recommend that the government should increase its recurrent expenditure on salaries, transfer payments and its investment spending on education, health, agricultural sectors and the provision of basic infrastructure in terms of construction of roads and bridges.
Keywords: government; capital expenditure; recurrent expenditure; economic growth